Placental insufficiency contributes to fatty acid metabolism alterations in aged female mouse offspring - Stojanovska, Violeta; Sharma, Neha; Dijkstra, Dorieke J.; Scherjon, Sicco A.; Jäger, Andrea; Schorle, Hubert; Plösch, Torsten (American journal of physiology. Regulatory, integrative and comparative physiology, 2018)
Intrauterine growth restriction (IUGR) is an accepted risk factor for metabolic disorders in later life, including obesity and type 2 diabetes. The level of metabolic dysregulation can vary between subjects and is dependent on the severity and the type of IUGR insult. Classical IUGR animal models involve nutritional deprivation of the mother or uterine artery ligation. The latter aims to mimic a placental insufficiency, which is the most frequent cause of IUGR. In this study, we investigated whether IUGR attributable to placental insufficiency impacts the glucose and lipid homeostasis at advanced age. Placental insufficiency was achieved by deletion of the transcription factor AP-2y ( Tfap2c), which serves as one of the major trophoblast differentiation regulators. TdelT-IUGR mice were obtained by crossing mice with a floxed Tfap2c allele and mice with Cre recombinase under the control of the Tpbpa promoter. In advanced adulthood (9–12 mo), female and male IUGR mice are respectively 20% and 12% leaner compared with controls. At this age, IUGR mice have unaffected glucose clearance and lipid parameters (cholesterol, triglycerides, and phospholipids) in the liver. However, female IUGR mice have increased plasma free fatty acids (+87%) compared with controls. This is accompanied by increased mRNA levels of fatty acid synthase and endoplasmic reticulum stress markers in white adipose tissue. Taken together, our results suggest that IUGR by placental insufficiency may lead to higher lipogenesis in female mice in advanced adulthood, at least indicated by greater Fasn expression. This effect was sex specific for the aged IUGR females.